Formation of the right second incisor root of the 9 years old girl after trauma complicated with periodontitis treated using mineral trioxide aggregate (LLC "Endo Press", 2020)
Сlinical case of treatment 9 years old girl with chronic periodontitis developed due to injury of the tooth 1.2. After examination the diagnose was: «Apical chronic periodontitis of tooth 1.2 K04.5.» according to ICD-C. Treatment plan was agreed with patient's parents. The course of undergoing treatment is described. Positive result was achieved after twenty-one months and confirmed radiologically.